Gastric Hyperplasia in Mice Lacking the Putative Cdc42 Effector IQGAP1 - Li, Shihong (American Society for Microbiology, 2000)
Human IQGAP1 is a widely expressed 190-kDa Cdc42-, Rac1-, and calmodulin-binding protein that interacts with F-actin in vivo and that can cross-link F-actin microfilaments in vitro. Recent results have implicated IQGAP1 as a component of pathways via which Cdc42 or Rac1 modulates cadherin-based cell adhesion (S. Kuroda et al., Science 281:832–835, 1998), whereas yeast IQGAP-related proteins have been found to play essential roles during cytokinesis. To identify critical in vivo functions of IQGAP1, we generated deficient mice by gene targeting. We demonstrate that IQGAP1 null mutants arise at normal frequency and show no obvious defects during development or for most of their adult life. Loss of IQGAP1 also does not affect tumor development or tumor progression, but mutant mice exhibit a significant (P < 0.0001) increase in late-onset gastric hyperplasia relative to wild-type animals of the same genetic background. While we cannot exclude that functional redundancy with IQGAP2 contributes to the lack of developmental phenotypes, the restricted expression pattern of IQGAP2 is not obviously altered in adult IQGAP1 mutant mice. Thus, IQGAP1 does not serve any essential nonredundant functions during murine development but may serve to maintain the integrity of the gastric mucosa in older animals.